Pemanfaatan Potensi Lahan Perkebunan Kelapa Sawit Di Kecamatan Basidondo Kabupaten Tolitoli - Apandi; Budianta, Aziz (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2024)
This research aims to determine the potential of oil palm plantation land located in Basidondo District, Tolitoli Regency, by weighting and overlaying mapping and looking at the economic value support. By using Land Suitability analysis which is then matched or matched to the land suitability matrix and land capabilities owned by Basidondo District, potential land use directions are obtained. This research is descriptive qualitative in nature with the geographical approach used being the Spatial Approach. This research uses observation techniques and literature review collection. The research results show that the actual land suitability class for oil palm plants in the research area has 1 (one) subclass, namely: Class S2 (quite suitable) at SPL 3 with a land area of ​​115,939.80 ha, and for SPL 4 with a land area of ​​11. 151,500 ha, generally limited by nutrient retention (f), available nutrients (n), and flooding. Class S3 (according to Marginal) is found at SPL 1 with a land area of ​​215,648.99 ha and SPL 2 with a land area of ​​442,386.00 ha, generally limited by nutrient retention (f), erosion hazard (e) slope, nutrient available (n).